The Comparison of Mycobacterium tuberculosis Detection using Molecular Rapid Test and Immunochromatography in Patients Suspected of Having Tuberculosis in Pangkajene and Kepulauan Regencies - Faradillah Suhar; Muhammad Nasrum Massi; Rizalinda Sjahril (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2021)
Mycobacterium tuberculosis is an acid-resistant bacterium that causes tuberculosis and can be detected using a variety of methods. This study aimed to determine the comparison of the detection results of Mycobacterium tuberculosis using the molecular rapid test (MRT) and immunochromatographic method. This research was conducted at Batara Siang Hospital, Pangkajene, and Kepulauan Regencies, in July-September 2019 using 100 samples. This study is cross-sectional research, applying the chi-square test for analysis. The results of statistical tests revealed a significant difference between the results of tests using molecular rapid tests and immunochromatography (<0.001). The sensitivity, specificity, positive probability value, negative probability value, and accuracy of the immunochromatography method against the molecular rapid test (MRT) were 91.3%, 100%, 100%, 93.1%, and 96%, respectively.